Reading the voice : Native American oral poetry on the page - Zolbrod, Paul G. (University of Utah Press, 1995)
This is a book about poetry: about its sacred underpinnings, its broad presence in everyday life, and its necessity to the human community. Reading the Voice examines poetry's abiding importance among Native Americans from ancient times to the present. It also seeks connections between an ancient tribal way of making and diffusing poetry and more recent print-oriented or electronic means. Drawing on years of experience with Seneca and Navajo singers and storytellers, Paul Zoibrod offers an introductory framework for appreciating what can be called America's first literature and for reevaluating the Western literary heritage. He states, "I consider this work a tentative first step in reconciling mainstream America with the deep poetic roots of an unwritten aboriginal past, and perhaps even with the deeper European roots of its own poetic traditions." To do so effectively, however, readers must first reexamine assumptions about what poetry and literature really are. Those who come to Native American "literature" in print must do so conscious of the dynamic sounds of speech and song by "reading the voice," instead of merely looking at a silent sheet of paper full of alphabetical symbols. By doing otherwise we stand to miss much that is essential to the verbal art of indigenous peoples whom print cultures approach from an alien perspective